2016
DOI: 10.18632/oncotarget.13128
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin disables prostate cancer maintenance by impairing proliferation and metabolic function

Abstract: Tristetraprolin (TTP) is an RNA-binding protein that post-transcriptionally suppresses gene expression by delivering mRNA cargo to processing bodies (P-bodies) where the mRNA is degraded. TTP functions as a tumor suppressor in a mouse model of B cell lymphoma, and in some human malignancies low TTP expression correlates with reduced survival. Here we report important prognostic and functional roles for TTP in human prostate cancer. First, gene expression analysis of prostate tumors revealed low TTP expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…TTP has also been suggested as a promising biomarker for prostate cancer risk assessment. TTP expression was markedly reduced in metastatic prostate cancer compared to primary tumors [64]. Men with low TTP-expressing primary prostate cancer had significantly increased chances of biochemical reoccurrence in this study.…”
Section: Ttp Family Proteins As Potential Biomarkersmentioning
confidence: 46%
See 1 more Smart Citation
“…TTP has also been suggested as a promising biomarker for prostate cancer risk assessment. TTP expression was markedly reduced in metastatic prostate cancer compared to primary tumors [64]. Men with low TTP-expressing primary prostate cancer had significantly increased chances of biochemical reoccurrence in this study.…”
Section: Ttp Family Proteins As Potential Biomarkersmentioning
confidence: 46%
“…Low-TTP in prostate cancer correlated with increased recurrence. Induced TTP expression reduced cell proliferation, clonogenic growth, and tumorigenic potential of prostate cancer cells [64].…”
Section: Prostate Cancer Ttp/zfp36mentioning
confidence: 96%
“…Next, we sought to further understand the mechanism of the tumor-suppressing function of TTP in the skin since increased inflammation was observed in grafts with knockdown of TTP in keratinocytes. We analyzed changes of cytokine expression and of metabolic genes, which have been reported to play crucial roles in TTP tumor-suppression function[ 18 , 23 ], in SCC13 skin tumor cells with modulations of TTP expression levels. We found that the knockdown of TTP in SCC13 cells induced the expression of the cytokines IL-8, TNFα, VEGF and COX2 ( S9A Fig ) as well as genes involved in metabolic pathways including the pyruvate dehydrogenase complex (PDK1), the citric acid cycle (IDH3A), the electron transport chain (GPD2), branched-chain amino acid metabolism (BCKDHB), purine biosynthesis (ADSS) and the pyrimidine salvage pathway (CMPK1) ( S9B Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…The aberrant over-expression of ARE-containing genes plays a crucial role in the initiation and progression of tumorigenesis [ 22 , 34 , 35 ]. A loss or decreased expression of TTP was observed in various epithelial tumors including breast, cervix, colon, liver, prostate and other cancers [ 18 , 22 , 23 , 35 , 36 ]. More and more evidence shows that the loss of TTP promotes tumorigenesis through multiple cancer-associated progressions including enhancing cancer cell proliferation by regulating IL-8, VEGF and COX2 production, and accelerating the cell cycle [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation